Design and Development of Heart Vest for Heart health Monitoring Based on Internet of Things (IoT) - Muhammad Iqbal Saputra P; Muhammad Miftahul Robih; Juju Juhaeriyah (Riviera Publishing, 2025)
IoT-based cardiac monitoring systems face the challenges of accuracy and convenience. The integration of real-time wearable based on AD8232 and ESP8266 has not been widely explored functionally. This research is important to develop a cheap, portable, and reliable heart monitoring solution. This research aims to design and test Heart Vest as a real-time heart monitoring system based on IoT and mobile applications. Experimental research was conducted by testing IoT devices based on AD8232 and ESP8266 sensors. Data is sent to Firebase and visualised through an Android application. Tests of sensor accuracy, data synchronisation, and BPM status classification are carried out to ensure system reliability. The test results show that the AD8232 sensor has an average accuracy of 97.8% (2.20% error). Data synchronisation between the Heart Vest LCD and the mobile application reached 100%. The system successfully classified the heart status (normal, alert, danger) with 100% accuracy and provided alerts via LED and buzzer. These findings demonstrate the reliability of the Heart Vest as an efficient, economical, and responsive real-time monitoring system in the context of non-clinical use. These findings strengthen the adoption of IoT wearable systems for cardiac monitoring. Further research needs clinical trials and multi-sensor integration.